Students’ Perceptions of the Da’irat al-Lughah Policy in Supporting Learning Motivation and Arabic Speaking Practice at Muhammadiyah Boarding School Yogyakarta/Persepsi Santri terhadap Kebijakan Da’irat al-Lughah dalam Mendukung Motivasi Belajar dan Praktik Berbicara Bahasa Arab di Muhammadiyah Boarding School Yogyakarta - Wahyuadi Setyaningtyas Dewi Putri; Kholisin Kholisin; Moch Wahib Dariyadi (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2025)
This study explores the implementation of Daʾirat al-Lughah in supporting students’ learning motivation and Arabic speaking confidence at Muhammadiyah Boarding School Yogyakarta. Employing a qualitative case study with a phenomenological perspective, the study involved language supervisors, student language committee members, and new students. Data were collected through observations, open-ended questionnaires, and supporting needs and response questionnaires. The findings indicate that Daʾirat al-Lughah fosters intrinsic motivation, habitual speaking practice, and confidence in using Arabic through a structured language environment beyond the classroom. Despite challenges related to language awareness, role modeling, and supervision, gradual habituation and program reinforcement supported the sustainability of the policy. This study underscores the role of a structured language environment in facilitating Arabic speaking practice in modern Islamic boarding schools.Penelitian ini mengkaji penerapan “Daʾirat al-Lughah” (Area Wajib Berbahasa) dalam mendukung motivasi belajar dan kepercayaan diri santri dalam berbicara bahasa Arab di Muhammadiyah Boarding School Yogyakarta. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus dan perspektif fenomenologis. Partisipan penelitian meliputi pembina bahasa, pengurus bidang bahasa, dan santri baru. Data dikumpulkan melalui observasi, angket terbuka, serta angket kebutuhan dan respon santri sebagai data pendukung. Hasil penelitian menunjukkan bahwa “Daʾirat al-Lughah” berkontribusi positif terhadap motivasi intrinsik, pembiasaan berbicara, dan rasa percaya diri santri dalam menggunakan bahasa Arab. Lingkungan bahasa yang terstruktur mendorong santri lebih aktif berkomunikasi di luar kelas. Meskipun terdapat tantangan dalam implementasi, strategi pembiasaan bertahap dan penguatan program membantu menjaga keberlangsungan kebijakan ini.